2004
DOI: 10.1038/nm984
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1-encoded p30II is a post-transcriptional negative regulator of viral replication

Abstract: Human T-cell leukemia/lymphoma virus type 1 (HTLV-1) persists despite a vigorous virus-specific host immune response, and causes adult T-cell leukemia and lymphoma in approximately 2% of infected individuals. Here we report that HTLV-1 has evolved a genetic function to restrict its own replication by a novel post-transcriptional mechanism. The HTLV-1-encoded p30(II) is a nuclear-resident protein that binds to, and retains in the nucleus, the doubly spliced mRNA encoding the Tax and Rex proteins. Because Tex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
211
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(214 citation statements)
references
References 27 publications
3
211
0
Order By: Relevance
“…In addition to Tax, HTLV-1 and HTLV-2 genomes also encode the p30 and p28 proteins, respectively (Nicot et al, 2004;Younis et al, 2004). Each of these two proteins has been shown to retain the doubly spliced mRNA encoding the Tax and Rex proteins in the nucleus.…”
Section: Characterization Of the Htlv/stlv-3 Tax Proteinmentioning
confidence: 99%
“…In addition to Tax, HTLV-1 and HTLV-2 genomes also encode the p30 and p28 proteins, respectively (Nicot et al, 2004;Younis et al, 2004). Each of these two proteins has been shown to retain the doubly spliced mRNA encoding the Tax and Rex proteins in the nucleus.…”
Section: Characterization Of the Htlv/stlv-3 Tax Proteinmentioning
confidence: 99%
“…In fact, studies of clonal expansion of HTLV-I-infected cells in HTLV-I carriers, demonstrate some clones persist for over 7 years in the same individual [86,87]. We have recently found that the virally encoded p30 protein prevents nuclear export of the tax/rex RNA and suppresses viral gene expression in vitro [88]. Whether or not p30 may act as latency factor in vivo remains to be investigated.…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…p30, expressed from a doubly-spliced mRNA, is a multifunctional regulator that differentially modulates viral and/or cellular gene expression at the transcriptional level through association with cellular proteins including p300/CBP and TIP60 (Awasthi et al, 2005;Zhang et al, 2001;Zhang et al, 2000) and post-transcriptionally via binding and retaining tax/rex mRNA in the nucleus (Nicot et al, 2004;Younis et al, 2006;Younis et al, 2004). Although p30 is dispensable in vitro for replication and cellular transformation (Derse et al, 1997;Robek et al, 1998), it is required to promote virus survival and persistence in infected animals (Silverman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%